Auricular L Graft as a Method of Extension of the Nasal Septum - Ortiz, Chiara Theresa Norato; García, Juan Sebastián Rivas; Rodriguez, Ana Cristina Eraso; Gonzalez, Ana Madeleine Quiñones; Arias, Edder Armando Pulido; Mansilla, Maria Camila Navarro; Valenzuela, Manuela Díaz; Espitia, María María Bernal (Jour Med Resh and Health Sci, 2022)
Plastic surgeries are performed in order to correct conditions in various body areas, defects related to accidents, trauma or birth defects, among these procedures is rhinoplasty, an area of ??facial cosmetic surgery that represents a challenge when it comes to practiced, this is considered one of the most performed practices in the field and at the same time of greater demands, among the procedures performed is the range of procedures specifically aimed at correcting the defects of the nasal septum "rhinoseptoplasty", by means of grafts, the The graft that is used most frequently is the autologous cartilage graft, which, in addition to being used as a filler, also has the necessary resistance to provide structural support, achieving an extension of it, thus correcting present anomalies, various studies and case reports have shown favorable results, when performing on terve tions using this method, The graft of auricular origin is harvested using different techniques depending on the amount of tissue that needs to be replaced, always trying to maintain the pre-surgical auricular anatomy. This type of graft is very useful in secondary rhinoplasties in which septal cartilage was developed in the first stage, this being no longer an option as a donor area, the use of "the L-shaped septal extension" is an alternative that should be widely used. used in the treatment of cases that require reconstruction and extension of the nasal septum, which is manifested in satisfactory results for the patient. These will be preserved over time, improving the aesthetic and functional status of the patient.